COMPARISON OF LEXICO-SEMANTIC PROCESSES OF INTERACTION OF PROFESSIONAL TERMS IN THE LANGUAGE FLOW IN MONITORING AND CONTROL OF AIR MOVEMENT - Зайцев, Ю. В. (Proceedings of National Aviation University (archive), 2021)
A comparative analysis of the lexical field of the two main areas of language training of air traffic controllers, which are used to form in air traffic controllers professional skills of operational analysis, decision-making and implementation of critical, emergency situations in air transport, communication in English with aircraft crews on international airlines.